Membangun Kesadaran Siswa Melalui Sosialiasi Pencegahan Pernikahan Dini Siswa Smpn 4 Arjasa Satu Atap Dampas Jatisari - Faidatul Hasanah; Makkiyah; Nuril Hamdiyah Ma’rufah; Faizul Abrori (Jurnal Inovasi dan Pengabdian, 2025)
This study aims to raise awareness among students of SMPN 4 Arjasa one roof, considering the prevalence of underage marriage among children, which can even be considered too early. This study focuses on how the Community Service Program (KKN) can educate students to be aware of their rights in rejecting something that is often considered cultural even though it clearly violates the law and human rights. The method used is descriptive qualitative with an approach through socialization and education, and efforts to prevent it. The results of the study indicate that this program is effective in upholding the rights of as a nation, daring to firmly reject things that violate the rule of law and daring to become a reporter if they become victims of forced underage marriage. This activity also succeeded in increasing students' self-confidence and courage to dream of continuing higher education without fear of being hindered by forced underage marriage. This activity effectively encourages students to dare to speak up and say "no" to underage marriage. This research is expected to reduce the number of underage marriages among children and students as well as in villages that normalize underage marriage.